Algeria : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that economic activity in Algeria has picked up in 2014, with real GDP growth projected to reach 4 percent following 2.8 percent growth in 2013. The hydrocarbon sector is expected to expand for the first time in eight years, while nonhydrocarbon growth remains supportive. Inflation has decelerated sharply to 2.1 percent, thanks in part to tighter monetary policy. The fiscal deficit is expected to widen to more than 7 percent owing to lower hydrocarbon revenue, a sharp increase in capital expenditure, and continued high current spending. Fiscal savings are expected to decline for the second consecutive year.